THE PEOPLE PEDAGOGICALLY EDUCATE YOUTH PATRIOTISM AND TRADITIONALLY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
In this article, examples of Karakalpak folk pedagogy are reflected in the traditions of patriotic education of young people based on the heroism of our ancestors in their struggle against external enemies.